1972
DOI: 10.1161/01.cir.45.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Demand Pacemakers by Inactive Pacemaker Electrodes

Abstract: Ventricular inhibited cardiac pacemakers were suppressed by intimate contact of the tip of the active pacemaker electrode with that of the inactive pacemaker electrode in two patients. This contact apparently was sensed as myocardial electrical activity and resulted in variable suppression of pacemaker emission. There was no interference with R-wave sensing function. The threshold for stimulation was unaffected. There was no loss of capture as tested with the magnet-controlled continuous mode of stimulation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…[72][73][74] Opponents of nonfunctional lead removal argue that the risk of electrical interference is avoided by eliminating contact between the active and abandoned leads and that this potential risk is not supported by available data. 34,45,46 In fact, physical lead-lead interaction is only 1 mechanism of spurious signal generation.…”
Section: Lead-lead Interactionmentioning
confidence: 99%
“…[72][73][74] Opponents of nonfunctional lead removal argue that the risk of electrical interference is avoided by eliminating contact between the active and abandoned leads and that this potential risk is not supported by available data. 34,45,46 In fact, physical lead-lead interaction is only 1 mechanism of spurious signal generation.…”
Section: Lead-lead Interactionmentioning
confidence: 99%
“…Patients with abandoned leads can associate asymptomatic venous thrombosis; moreover, the association of multiple leads significantly increases the risk of asymptomatic venous occlusion and also infection [ 21 ]. It was observed that, in the case of lead abandonment, there is a risk of electrical interference between active and abandoned leads that can result in the oversensing and inappropriate inhibition of pacing with potentially severe consequences [ 22 ].…”
Section: Indications For Lead Extractionmentioning
confidence: 99%
“…Partial electrode fracture may lead to defective pacing ( 3 , 8, 27, 33, 3 7 ) , as the difference in potential arising from a sudden change in electrode resistance may disturb the demand mechanism, and thus inhibit a QRS-inhibited pacemaker or trigger a QRS-triggered pacemaker. Widman et al (51) have reported that failure of demand function in 2 patients was caused by intimate contact of the tip of the active pacemaker electrode with that of the inactive electrode. This was probably due to a change in the electrical resistance associated with intermittent contact of two bipolar catheter tips.…”
Section: Failure Due To Electrodementioning
confidence: 99%